User-fee-funded stormwater programs (Special publication (Water Environment Federation), 2013)
A must-read for agencies and public works departments interested in developing charge systems for stormwater programs based on fee structures. This book will specify the drivers for stormwater user-fee formation and explore the responsibilities, costs, and entire implementation process.